High repetition rate high-order harmonic generation up to the carbon K-edge in an antiresonant hollow-core fiber - Gebhardt, Martin; Heuermann, Tobias; Klas, Robert; Kirsche, Alexander; Liu, Chang; Wang, Ziyao; Lenski, Mathias; Gaida, Christian; Jauregui, Cesar; Antonio-Lopez, Jose; Schülzgen, Axel; Amezcua-Correa, Rodrigo; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2021)
Intense, ultrafast laser sources with an operation wavelength beyond the well-established near-IR are valuable tools for exploiting the wavelength scaling laws of strong-field, light-matter interactions. Such laser systems enable the scaling of the phase matching photon energy cut-off in high-order harmonic generation, which allows for the generation of coherent soft X-ray radiation up to, and even beyond, the water window. Such laser-driven sources enable a plethora of subsequent applications. A number of these applications can significantly benefit from an increase in repetition rate. In that regard, ultrafast thulium-doped fiber laser systems (providing a broad amplification bandwidth in the 2 μm wavelength region) represent a promising, average-power scalable laser concept for driving high-order harmonic generation. These lasers are capable of delivering ∼100 fs pulses with multi-GW peak power at hundreds of kHz repetition rate. In this work, we show that combining ultrafast thulium-doped fiber CPA systems with HHG in an antiresonant hollow-core fiber is a promising approach to realize high photon energy cut-off HHG from a compact setup. The realization is based on combining nonlinear pulse self-compression (leading to strong-field waveforms) and phase-matched high-order harmonic generation in a single antiresonant hollow-core fiber. In this demonstration, a photon energy cut-off of approximately 330 eV has been achieved, together with a photon flux >106ph/s/eV at 300 eV. These results emphasize the great potential of exploiting the HHG wavelength scaling laws with 2 μm fiber laser technology. Improvements of the HHG efficiency, the overall HHG yield and further laser performance enhancements will be the subjects of our future work.
CRIS-Team Scopus Importer:2023-04-20
Keywords: High harmonic generation; High-power fiber laser; Hollow-core fiber; Soft X-rays